Legal Protection of Foreign Investors in Southeast Asia: A Comparative Analysis of Investor-State Dispute Settlement (ISDS) Mechanisms - Oli, Anthony (PT. Batari Edu Calya, 2025)
Southeast Asia has become a focal point for foreign direct investment (FDI) due to its robust economic growth, political stability, and the integration promoted by the ASEAN Economic Community (AEC). However, investment across borders entails significant legal risks, particularly disputes between investors and host states arising from regulatory changes, expropriation, or discriminatory measures. To mitigate these risks, ASEAN member states rely on Investor-State Dispute Settlement (ISDS) mechanisms embedded in international treaties such as Bilateral Investment Treaties (BITs), the ASEAN Comprehensive Investment Agreement (ACIA), and the Regional Comprehensive Economic Partnership (RCEP). This article employs a normative-legal methodology with a comparative approach to examine ISDS provisions across ASEAN jurisdictions. The findings reveal divergent national practices: Indonesia has limited its BIT commitments to safeguard its sovereignty, Singapore provides expansive protections for investors, while Vietnam, Malaysia, and Thailand adopt moderate stances that balance investor rights with domestic regulations. ISDS has proven effective in providing investors with neutral arbitration avenues, but it also raises challenges, including high arbitration costs, regulatory chill, and limited transparency. The study concludes that ASEAN requires harmonisation of investment frameworks, enhanced transparency, and the strengthening of alternative dispute resolution mechanisms to balance investor protection with state sovereignty